2013
DOI: 10.1186/ar4244
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of patients with active ankylosing spondylitis with etanercept-sustained efficacy and safety after seven years

Abstract: IntroductionData from clinical studies on the long-term efficacy and safety of anti-tumor necrosis factor (TNF)-α therapy in patients with ankylosing spondylitis (AS) are scarce. This is the first report on continuous treatment with the TNFα fusion protein etanercept over seven years (y).MethodsOverall, 26 patients with active AS were initially treated with etanercept 2 × 25 mg s.c./week with no concomitant disease modifying anti-rheumatic drugs (DMARDs) or steroids. The clinical response was assessed by stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 32 publications
2
28
0
5
Order By: Relevance
“…Tumor Necrosis Factor Inhibitor Withdrawal or Dose Reduction in Axial Spondyloarthritis. Long-term extension studies have shown sustained clinical efficacy of TNF inhibitors in patients who continue treatment (Baraliakos et al, 2011a(Baraliakos et al, , 2013a. A number of small and open-label extension studies have evaluated withdrawal of TNF inhibitors in AS and axSpA patients who are in remission.…”
Section: A Ankylosing Spondylitis and Axial Spondyloarthritismentioning
confidence: 99%
“…Tumor Necrosis Factor Inhibitor Withdrawal or Dose Reduction in Axial Spondyloarthritis. Long-term extension studies have shown sustained clinical efficacy of TNF inhibitors in patients who continue treatment (Baraliakos et al, 2011a(Baraliakos et al, , 2013a. A number of small and open-label extension studies have evaluated withdrawal of TNF inhibitors in AS and axSpA patients who are in remission.…”
Section: A Ankylosing Spondylitis and Axial Spondyloarthritismentioning
confidence: 99%
“…For example, several longterm followup studies on anti-TNF now exist 45 and uniformly show a mean BASFI of about 7/10 at baseline which, after initial therapy response, remains stable at about 3/10 during the 8-year followup. In contrast, performance-based tests in AS may be more sensitive to change because they are able to detect improvement even in nonresponders 21 during anti-TNF therapy at 3 months of followup, although learning effects could not be excluded.…”
Section: Rheumatologymentioning
confidence: 95%
“…В исследовании Х. Baraliakos и соавт. [3] был продемонстрирован устойчи-вый эффект длительного (>7 лет) применения ЭТЦ: ста-бильная эффективность по всем критериям улучшения АС была получена у 62% пациентов, частичная ремиссия по критериям ASAS -у 31,3% пациентов, низкая актив-ность по ASDAS -у 43,8% пациентов, сохранение BASDAI <3 и умеренной активности по ASDAS -у 68,8% пациентов. Полученные результаты свидетельствуют о высокой эффективности и хорошей переносимости препарата.…”
Section: Discussionunclassified
“…[2] было показано, что стойкий ответ по критери-ям Международного общества по оценке спондилоартри-тов (ASAS) на фоне терапии ЭТЦ сохранялся в течение 4 лет, причем частичная ремиссия наблюдалась у 44% паци-ентов, 40% улучшение по критериям ASAS и 50% сниже-ние BASDAI получено у 69% пациентов [2]. Одно из самых длительных наблюдений за эффективностью и переноси-мостью ЭТЦ у больных АС, начавшееся в 2005 г. в Герма-нии, продолжается свыше 10 лет, при этом более 7 лет те-рапию получали 62% больных (16 из 26), у трети из них со-хранялась клиническая ремиссия, у 44% -низкая актив-ность анкилозирующего спондилита (АС) [3]. ЭТЦ, в отли-чие от моноклональных антител (мАТ), стабильно снижает активность заболевания даже при возобновлении терапии после годичного перерыва [4], что может быть связано с более низкой, по сравнению с мАТ, выработкой антиней-трализующих антител [5].…”
unclassified